Spectroscopic dataset of Hedione's derivatives gathered during process development - James S. Sharley; Guido Gambacorta; Ana María Collado Pérez; Estela Espinos Ferri; Amadeo Fernandez Miranda; Jorge Sanchez Quesada; Ian R. Baxendale (Data in Brief, 2023)
The dataset of spectroscopic analysis performed on starting materials, intermediates, and products relating to the synthesis of Hedione are hereby presented. The data were acquired in Durham university during the period between October 2020 and September 2021 for the development of a preparative method to Dehydrohedione. The latter is a key intermediate for the synthesis of cis-Hedione, an important fragrance ingredient. Proton, Carbon-13, and Fluorine-19 Nuclear magnetic resonance of the compounds were recorded employing a Varian 600 MHz, and a Bruker Avance-400 instrument. The IR spectra were recorded in a Perkin Elmer Spectrum Two UATR Two FT-IR and the accurate mass employing a Waters QtoF premier as mass spectrometer.